American English vs. British English: principal differences and the confusions / Faridah Yahaya - Yahaya, Faridah (2003)
British English (BE) and American English (AE) are variants of the English Language. There are really very few differences between standard British English and standard American English. However, the largest difference is probably that of the choice of vocabulary, spelling and pronunciation. As these two variants are being used interchangeably and extensively in Malaysia, these differences have caused confusions among students and lecturers. Students tend to think that one version is better than the other. It takes some time for the lecturers to persuade their students that the difference between the two is largely lexical, and that they should use the one, which they find easier and be consistent in their use. As lecturers often encounter problems in pointing out these differences to their students in their teaching, this paper offers a guide to point out the principal differences between these two varieties of English. It is hoped that further information concerning these areas will help ease the confusions in the classroom teaching and learning instructions.